ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PREFERENSI NASABAH DALAM MEMILIH PRODUK PEMBIAYAAN MURABAHAH - maulana, aulia rachman (Islamic Economics and finance in Focus, 2023)
This study aims to identify the factors that influence customer preferences in using murabahah financing products at Bank Muamalat Kota Batu. The factors studied in this research are service quality and financing product quality. The population of this study is the customers of Bank Muamalat Kota Batu. The sample size used in this research is 50 people selected using purposive sampling. The research method used is descriptive quantitative. The research data is primary data obtained from distributing questionnaires. The questionnaire is designed using a Likert scale of 1-5. The collected data is then analyzed using validity test, reliability test, assumption test, and multiple linear regression analysis with the help of SPSS statistical calculation application. The results show that service quality and financing product quality have a significant influence on customer preferences in using murabahah financing products. The better the service quality and financing product quality, the higher the customer preference in using murabahah financing products. Therefore, Bank Muamalat Kota Batu needs to pay attention to and improve the service quality and financing product quality to meet customer needs and increase customer preferences in using murabahah financing products.